Problems of a New Paradigm in the Legal Village Asset Management - Nahuddin, Yusuf Eko; SA, Romli; Agung, Muhammad Maghfur (Universitas Islam Negeri Raden Fatah Palembang, 2023)
Independent management of village assets in order to make the village the main locomotive for the welfare of the village community is a necessity, while the purpose of this study is to find out how the new paradigm in village asset management and what is a problem in village asset management. This research method uses a type of normative legal research with a statutory approach and a conceptual approach. By collecting legal materials that are relevant to the issues raised and read and then grouped before being interpreted and analyzed using qualitative methods. This research concluded that the new paradigm in village asset management must be understood by all village asset management power holders so that village assets can be managed optimally to increase the potential source of village income so that it becomes an independent village. However, the new paradigm still causes problems including the old mindset in managing village assets and the still weak supervision in the management of village assets and the data collection of village assets that are not optimal, not to mention the conditions where inhumanity in the management of village assets by the holders of village asset management power For this reason, it is necessary to encourage technology-based village asset management management (digitalization) so that there are the same standards, the same perspective in village asset management , so as to give birth to the creativity of village asset management power holders in optimizing the potential of their village assets independently so that the village becomes a locomotive of development and equitable distribution of the welfare of the rural community.